Two random repeat recall methods to assess alcohol use. - Midanik, L T (1993)
Two random repeat recall methods were compared with a summary measure to assess alcohol use. Subjects (n = 142) were randomly assigned to one of two groups; they were called either on 14 random days during three 30-day waves and asked about drinking yesterday, or on 2 random days during each wave and asked about drinking in the past week. Follow-up telephone interviews obtained summary measures for each wave. Random repeat methods generally obtained higher estimates. However, the high dropout rate makes questionable the feasibility of using this approach with general population samples.